Volcanic arcs fed by rapid pulsed fluid flow through subducting slabs - John, Timm; Gussone, Nikolaus; Podladchikov, Yuri Y.; Bebout, Gray E.; Dohmen, Ralf; Halama, Ralf; Klemd, Reiner; Magna, Tomas; Seitz, Hans-Michael (Nature Geoscience, 2012)
At subduction zones, oceanic lithosphere that has interacted with sea water is returned to the mantle, heats up during descent and releases fluids by devolatilization of hydrous minerals. Models for the formation of magmas feeding volcanoes above subduction zones require largescale transport of these fluids into overlying mantle wedges 1-3. Fluid flow also seems to be linked to seismicity in subducting slabs. However, the spatial and temporal scales of this fluid flow remain largely unknown, with suggested timescales ranging from tens to tens of thousands of years 3-5. Here we use the Li-Ca-Sr isotope systems to consider fluid sources and quantitatively constrain the duration of subduction-zone fluid release at ∼ 70 km depth within subducting oceanic lithosphere, now exhumed in the Chinese Tianshan Mountains. Using lithium-diffusion modelling, we find that the wall-rock porosity adjacent to the flowpath of the fluids increased ten times above the background level. We show that fluids released by devolatilization travelled through the slab along major conduits in pulses with durations of about ∼ 200 years. Thus, although the overall slab dehydration process is continuous over millions of years and over a wide range of pressures and temperatures, we conclude that the fluids produced by dehydration in subducting slabs are mobilized in short-lived, channelized fluid-flow events. © 2012 Macmillan Publishers Limited. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.c3geoc.volcan